Analisis Opini Tidak Memberikan Pendapat BPK RI terhadap Laporan Keuangan Kabupaten Kepulauan Meranti - Monalika, Hani Putri (Penerbit Goodwood, 2024)
Purpose: This study aims to examine and analyze the Follow-up on the Audit Report of the Indonesian Supreme Audit Agency (BPK RI) on the Local Government Financial Report (LKPD) of the Kepulauan Meranti Regency, as well as to assess the level of transparency and accountability in financial performance reporting.Research methodology: This research uses a descriptive qualitative approach, employing document study or content analysis, and in-depth interviews with stakeholders such as auditors.Results: The audit opinion was a